DINA, PERANCANGAN SISTEM INFORMASI PERHITUNGAN PENCAPAIAN TARGET TOKO MENGGUNAKAN PHP DAN MYSQL DI ALFAMART SELAAWI GARUT - DINA NURFITRIANA (INFOKOM (Informatika & Komputer), 2018)
This study aims to design the information system of the achievement of the target store inAlfamart Selaawi, Garut. To design this information system used Data Flow Diagram asmodeling method and waterfall method as its design method.This system uses PHP as aprogramming application with MySQL as its database. The input data required in thissystem is the target store data and daily data. After the two data inputted, the process ofcalculating the target, by comparing the daily data with the target data that has beeninputted previously. The resulting output is a daily and monthly target achievementreport. This report is useful to find out how far the store reaches the given target. It isalso used as a basis for decision-making related to the achievement of these targets.